Design and simulation of a compact patch antenna for breast cancer tumors detection in the Wi-Fi band - Salima Azzaz-Rahmani; Hadj Zerrouki (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
The escalating need for safe, low-cost, and reliable medical diagnostic tools has propelled research into microwave imaging (MWI) for breast cancer detection. This study aims to design and evaluate, via simulation, a compact microstrip patch antenna operating in the 2.4 GHz wireless fidelity (Wi-Fi) band as a preliminary sensing element. The antenna, with overall dimensions of (14×14×3.1) mm³, is designed on a Rogers RT/duroid 5880 substrate and superstrate (ε_r= 2.2). To evaluate its detection capabilities, the antenna is placed over a simplified three-layer human breast phantom (skin, fat, and fibro-glandular tissue). Using Ansys high frequency structure simulator (HFSS) software, three scenarios were simulated: a healthy breast, a breast with a single tumor, and a breast with two tumors. The simulation results indicate measurable shifts in electromagnetic parameters used as diagnostic indicators. The presence of tumors caused a shift in the resonant frequency (from 2.42 GHz to 2.46 GHz) and a variation in the reflection coefficient (S11) magnitude. Specifically, the antenna demonstrates high sensitivity to dielectric loading changes, identified by a performance framework that correlates frequency shifts to tumor presence, while maintaining specific absorption rate (SAR) values within safety limits. This work demonstrates, through simulation, the feasibility of using a compact Wi-Fi band patch antenna for breast tumor detection, providing a foundation for future experimental development of portable diagnostic systems.